2010
DOI: 10.5539/ijbm.v5n8p57
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Turnover Intention among Private Sector Employees

Abstract: This study aims to study the organizational commitments, job stress, job satisfaction and turnover intention among the private sector employees in Petaling. A total of 120 respondents in Petaling District were selected conveniently. Organizational Commitments Questionnaire (Mowday, Steers & Porter, 1979), perceived Stress Scale (PSS), Minnesota Satisfaction Questionnaire (MSQ) and Mobley, Horner & Hollingsworth (1978) were used to measure organizational commitments, job stress, job satisfaction, and turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 2 publications
6
70
0
8
Order By: Relevance
“…Variables used in this study were quality of work life (with six indicators that were management leadership-values, work pressures, autonomy-fulfilment, salary, pride in organization, and happiness and progress), 17 psychological well-being (with six indicators that were self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth), 18 and turnover intention (with one indicator that was turnover intention). 11,19 Measurement category of respondent's distribution using criteria low (1.00-2.33), medium (2.34-3.67), and high (3.68-5.00). 20 The conceptual framework is shown at Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Variables used in this study were quality of work life (with six indicators that were management leadership-values, work pressures, autonomy-fulfilment, salary, pride in organization, and happiness and progress), 17 psychological well-being (with six indicators that were self-acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, and personal growth), 18 and turnover intention (with one indicator that was turnover intention). 11,19 Measurement category of respondent's distribution using criteria low (1.00-2.33), medium (2.34-3.67), and high (3.68-5.00). 20 The conceptual framework is shown at Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…All of the previous studies assessed employees' turnover intention from their self-reported measures [e.g. 5,10,12,22,45] and reported the possibility of common method bias, which can lead towards misleading information and results. We argued that due to collective culture of South Asia, people share their feelings and intentions with others close to them.…”
Section: Discussionmentioning
confidence: 99%
“…Organizational scholars and practitioners have shown a burgeoning attention to satisfy and retain key performer as the cost of leaving a job is very high for both; the employee itself and for the employing organizations [2]. Employee retention is coveted as the organizations invest lots of money and effort, directly or indirectly, on employees' recruitment, selection, training and development [3][4][5]. Turnover costs suffered by the organizations incorporate departure costs (post quit surveys, administrative time, and reserved salary), replacement costs (training expenses), and staffing costs (publicizing costs, the amount of time spent, test evaluation, candidate screening, individual verification, travel expenses [6].…”
Section: Introductionmentioning
confidence: 99%
“…This particular intention occurs as a result of strong job dissatisfaction (Hassan et al, 2015;Choong et al, 2012) and poor organizational http://dx.doi.org/10.15405/epsbs.2018.05.19 Corresponding Author: Michael Teng Selection and peer-review under (Lew, 2009;Yin-Fah et al, 2010). In specific, the turnover intention among Malaysian academicians of private higher education institutions (PHEIs) is in critical stage (Hashim & Mahmood, 2011).…”
Section: Introductionmentioning
confidence: 99%